Recent advances in carrageenan-based films for food packaging applications - Cheng, Cheng; Chen, Shuai; Su, Jiaqi; Zhu, Ming; Zhou, Mingrui; Chen, Tianming; Han, Yahong (Frontiers in Nutrition, 2022)
In order to solve the increasingly serious environmental problems caused by plastic-based packaging, carrageenan-based films are drawing much attentions in food packaging applications, due to low cost, biodegradability, compatibility, and film-forming property. The purpose of this article is to present a comprehensive review of recent developments in carrageenan-based films, including fabrication strategies, physical and chemical properties and novel food packaging applications. Carrageenan can be extracted from red algae mainly by hydrolysis, ultrasonic-assisted and microwave-assisted extraction, and the combination of multiple extraction methods will be future trends in carrageenan extraction methods. Carrageenan can form homogeneous film-forming solutions and fabricate films mainly by direct coating, solvent casting and electrospinning, and mechanism of film formation was discussed in detail. Due to inherent limitations of the pure carrageenan film, physical and chemical properties of carrageenan films were enhanced by incorporation with other compounds. Therefore, carrageenan-based films can be widely used for extending the shelf life of food and monitoring the food freshness by inhibiting microbial growth, reducing moisture loss and the respiration etc. This article will provide useful guidelines for further research on carrageenan-based films.